Analysis of Teacher's Readiness for 2013 Curriculum Thematic Learning in SD Negeri 04 Kriyan Kalinyamatan Jepara - Rahmawati, Zuli Agustin; KHB, Moh Aniq; Endah H, Diana (LPPM Undiksha, 2019)
This research was motivated by the readiness of teachers in the implementation of the 2013 curriculum thematic learning at SD Negeri 04 Kriyan Kalinyamatan Jepara. The problem in the research is